Aflasafe KE01 for Kenya - CGIAR Research Program on Agriculture for Nutrition and Health (2019)
The Aflasafe KE01 factory was officially opened by the Minister of Agriculture and Irrigation and the United States Agency for International Development (USAID) Mission Director. The plant, managed by the Kenya Agricultural and Livestock Research Organization, manufactures and distributes Aflasafe KE01. In 2019, another new distribution partner was appointed.